Three echoes listening to the geometric re-statement of nature - Lizasoain, Joaquín (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
Three projects -a Museum for Unlimited Growth, by Le Corbusier, a Chapel at the Camino de Santiago, by Oiza, Oteiza and Romany, and a Relaxation Park in Torrevieja, by Toyo Ito - share the seashell as a metaphor of nature, meaning in some way, the constant whispers of natural forms´geometries as a source of inspiration to achieve new architectural approaches. Although the three examples could be included in the same architectural family -in a similar way as animals are classified in nature-, setting a specific net of connections, each one provides a singular vision that serves to explain a different way of understanding its relationship with nature. A new habitat for the world can be recognized in the vital development of this kind of architectural approach. By this procedure, nature and architecture will keep sharing, repeatedly, common laws with new points of view.